A novel microRNA, SlymiR208, promotes leaf senescence via regulating cytokinin biosynthesis in tomato. Issue 2 (15th February 2020) - Zhang, Yong; Yin, Shuangqin; Tu, Yun; Mei, Hu; Yang, Yingwu
Abstract : Leaf senescence is a highly‐programmed developmental process during the plant life cycle. Cytokinin (CK) has been widely acknowledged as a negative regulator to delay leaf senescence. MiRNAs play key roles in a variety of developmental and physiological processes through negatively regulating their target gene expression. However, to date, the roles of microRNAs (miRNAs) in CK biosynthesis remain unclear, and the knowledge on miRNA regulation of leaf senescence is still very limited. Isopentenyltransferases (IPTs) catalyze the initial and rate‐limiting step of CK biosynthesis in higher plants. Our previous work uncovered that silencing of SlIPT4 expression in tomato resulted in premature leaf senescence. Here, we identified a novel tomato miRNA, SlymiR208, which regulates the expression of SlIPT2 and SlIPT4 at the post‐transcriptional level. SlymiR208 expression is ubiquitous in tomato and exhibits an opposite transition to its target transcripts in aged leaf. SlymiR208 overexpression in tomato sharply reduced the transcript levels of SlIPT2 and SlIPT4, and the concentrations of endogenous CKs in leaves. The early leaf senescence caused by SlymiR208 overexpression was consistent with the phenotype of SlIPT4 ‐silenced lines. The data demonstrated that SlymiR208 is a positive regulator in leaf senescence through negatively regulating CK biosynthesis via targeting SlIPT2 and SlIPT4 in tomato. This study indicated that post‐transcriptional regulation via miRNA is a control point of CK biosynthesis and added a new layer to the understanding of the regulation of CK biosynthesis in tomato and a new factual proof to support that miRNAs are involved in leaf senescence.